Woman with Power to Construct and Exercise Strategies as Portrayed in 7 Wonders - Alicia Nagaseta; Liliek Soelistyo (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
As a modernized version of the folktale Jaka Tarub dan Tujuh Bidadari, 7 Wonders applies the view that women should perform the Javanese concept of three Ms: masak, macak, and manak to please men while also acting weak around them. However, in the story, Nawang Wulan’s actions do not indicate that she is weak. Instead, she can prove that she is a powerful woman who can construct her strategies to reach her goals. Thus, this study aims to discuss that the Nawang Wulan’s strategies are altering their looks, using her support, and acting as weak woman. Each of the strategy displays her power and freedom to use the Javanese concepts of three Ms to please Jaka Tarub. As a result, she can persuade the him to help her reach her goals, and thus proves that her strategies can be used to control the him.Keywords: Folktale, Girl Power, Men, Strategy, Women